Identification of Antimutagenic Properties of Anthocyanins and Other Polyphenols from Rose (Rosa centifolia) Petals and Tea. Issue 6 (29th April 2013) - Kumar, Sanjeev; Gautam, Satyendra; Sharma, Arun
Abstract Petals from different rose (Rosa centifolia) cultivars ("passion, " "pink noblesse, " and "sphinx") were assessed for antimutagenicity using Escherichia coli RNA polymerase B (rpoB)‐based Rif S→Rif R (rifampicin sensitive to resistant) forward mutation assay against ethyl methanesulfonate (EMS)‐induced mutagenesis. The aqueous extracts of rose petals from different cultivars exhibited a wide variation in their antimutagenicity. Among these, cv. "passion" was found to display maximum antimutagenicity. Upon further fractionation, the anthocyanin extract of cv. "passion" displayed significantly higher antimutagenicity than its phenolic extract. During thin‐layer chromatography (TLC) analysis, the anthocyanin extract got resolved into 3 spots: yellow (Rf: 0.14), blue (Rf: 0.30), and pink (Rf: 0.49). Among these spots, the blue one displayed significantly higher antimutagenicity than the other 2. Upon high‐performance liquid chromatography analysis, this blue spot further got resolved into 2 peaks (Rt: 2.7 and 3.8 min). The 2nd peak (Rt: 3.8 min) displaying high antimutagenicity was identified by ESI‐IT‐MS/MS analysis as peonidin 3‐glucoside, whereas less antimutagenic peak 1 (Rt: 2.7) was identified as cyanidin 3, 5‐diglucoside. The other TLC bands were also characterized by ESI‐IT‐MS/MS analysis. The least antimutagenic pink band (Rf: 0.49) was identified as malvidin 3‐acetylglucoside‐4‐vinylcatechol, whereas non‐antimutagenic yellow band (Rf: 0.14) was identified as luteolinidin anthocyanin derivative. Interestingly, the anthocyanin extracted from rose tea of cv. "passion" exhibited a similar antimutagenicity as that of the raw rose petal indicating the thermal stability of the contributing bioactive(s). The findings thus indicated the health protective property of differently colored rose cultivars and the nature of their active bioingredients.